2010
DOI: 10.1136/oem.2010.057075
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of physical workload and occupational noise in the association of the metabolic syndrome with risk of coronary heart disease: findings from the Helsinki Heart Study

Abstract: Occupational exposure to workload or noise modifies CHD risk differently depending on which definition of MetS is used. In the presence of physical workload or noise, hypertension and blood glucose were the best predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
3
6
0
Order By: Relevance
“…In the study, we found the percentage of hypertension in the noise exposure group was significantly higher than the control group. This result was in accordance with previous studies [9,[24][25][26][27]. These studies reported that there was a positive relation between hypertension and noise exposure, and some of them analyzed the possible reasons.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the study, we found the percentage of hypertension in the noise exposure group was significantly higher than the control group. This result was in accordance with previous studies [9,[24][25][26][27]. These studies reported that there was a positive relation between hypertension and noise exposure, and some of them analyzed the possible reasons.…”
Section: Discussionsupporting
confidence: 82%
“…When MetS defined by high triglycerides, BMI and low HDL-C, the occupational noise exposure has a protective effect and can decrease the risk of CHD. While if MetS defined by high blood pressure, BMI and glucose, no protective effect is shown [26], and when noise exposure above 80 dB (A) correlated with hypertension and 4000 HZ has the most enormous effect [9]. All these are the possible reasons for why noise could impact blood pressure of people.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Li et al also supported our study by concluding that significant effect of noise is related to increased prevalence of MetS [27]. Moreover, An 18-year follow-up study concluded that hypertension and BS, key components of MetS, are the best predictors for assessment of the risk of coronary heart disease due to continuous exposure to occupational noise in support to our study [28].…”
Section: Discussionsupporting
confidence: 76%
“…Although this study supports our result that BMI group of overweight is independently associated with prevalence of hypertension. A study done in Finland also suggested that the work load and occupational noise is responsible for the increased risk of coronary heart disease due to increased blood pressure, BMI and glucose level [46]. A multivariate analysis in a study publicized that age, body mass index, cumulative noise exposure, current antihypertensive medication and alcohol intake were the significant predictors for systolic blood pressure [47].…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to 40-55 dB shows acute rise in adverse health consequences and also the vulnerable groups inclines to be intensely affected. The upsurge of the noise level above 55 dB has recurrent contrary health outcomes with elevated per centum of annoyance in huge population group [46,48]. A cross-sectional study carried out in one of the screw manufacturing factory in Taiwan with 188 male workers showed that the noise exposure of ≥ 80 dB for 2-4 years have a higher risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%